2016
DOI: 10.1039/c5gc01373a
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne polyurethanes from CO2 based polyols with comprehensive hydrolysis/oxidation resistance

Abstract: 5Carbon dioxide based oligo(carbonate-ether) diol (CO 2 -polyol) with both carbonate units and ether units in one polymer chain were prepared from copolymerization of CO 2 and propylene oxide (PO) using zinccobalt double metal complex as catalyst, and used to prepare CO 2 based waterborne polyurethane (CO 2 -WPU). The carbonate units in CO 2 -polyol improved the mechanical and oxidation resistance properties of CO 2 -WPU, while the ether units in CO 2 -polyol enhanced the hydrolysis resistance of CO 2 -WPU. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 38 publications
0
70
0
Order By: Relevance
“…341 The advantages of CO 2 -based poly(carbonateether)s as polyols for polyurethane synthesis over their polyester and polyether counterparts was further demonstrated by synthesising a series of polyurethanes from poly( propylene carbonate-ether) polyols and comparing them with polyurethanes incorporating polyester ( poly(butylene adipate glycol)) or polyether ( poly( propylene oxide glycol)) segments. 326 It was observed that the polycarbonate-based polyurethane (with 66% carbonate linkages and 34% ether linkages) exhibited better mechanical properties, although with a lower elongation at break compared to the other two polyurethanes, indicating a more rigid plastic behaviour (Table 10, entries 9-11). In addition, the poly(carbonate-ether)-based polyurethane exhibited better resistance against hydrolysis and oxidation compared to the polyester and polyether polyurethanes, which was ascribed to the presence of ether linkages with good hydrolysis resistance and to the relatively hydrophobic and rigid propylene carbonate repeating units, which might limit the permeation of water and, thus, increase the hydrolysis and oxidation resistance.…”
Section: Green Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…341 The advantages of CO 2 -based poly(carbonateether)s as polyols for polyurethane synthesis over their polyester and polyether counterparts was further demonstrated by synthesising a series of polyurethanes from poly( propylene carbonate-ether) polyols and comparing them with polyurethanes incorporating polyester ( poly(butylene adipate glycol)) or polyether ( poly( propylene oxide glycol)) segments. 326 It was observed that the polycarbonate-based polyurethane (with 66% carbonate linkages and 34% ether linkages) exhibited better mechanical properties, although with a lower elongation at break compared to the other two polyurethanes, indicating a more rigid plastic behaviour (Table 10, entries 9-11). In addition, the poly(carbonate-ether)-based polyurethane exhibited better resistance against hydrolysis and oxidation compared to the polyester and polyether polyurethanes, which was ascribed to the presence of ether linkages with good hydrolysis resistance and to the relatively hydrophobic and rigid propylene carbonate repeating units, which might limit the permeation of water and, thus, increase the hydrolysis and oxidation resistance.…”
Section: Green Chemistrymentioning
confidence: 99%
“…336 A general drawback of polyurethane formulations for foams is that products prepared with polyesters as polyols exhibit excellent mechanical properties but poor hydrolysis resistance, while polyurethanes prepared using polyethers as polyols possess proper hydrolysis resistance but insufficient oxidation resistance and display poor mechanical properties. 326,327 Since CO 2 -epoxide-based polycarbonates share similarities with both polyesters and polyethers with regard to the chemical structure but have lower tendency to hydrolyse compared to polyesters, polycarbonate polyols have been investigated as an alternative to conventional polyester and polyether polyols. Additionally, employing CO 2 -based poly(carbonate-ether) polyols is a greener option, as it allows increasing the renewable content of the polymer (up to 43 wt% CO 2 in the case of poly( propylene carbonate)).…”
Section: Green Chemistrymentioning
confidence: 99%
“…PU is usually prepared by the step‐growth polymerization of isocyanates with two or more NCO groups with petroleum‐based polyols . Due to the rapid consumption of fossil resources and serious environmental pollution, intensive interest has been paid to developing bio‐based polyols from renewable resources for preparing PU . The most popular renewable polyols are currently derived from plant oil .…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, the PEC polyols exhibit better hydrolysis resistance and oxidative stability compared with polyester- and polyether-type polyols. 19 Chemical and oxidative stability derived from PEC polyols are important and highly desirable properties in PU applications. Therefore, the PEC polyols represent substitutable and sustainable polyols, which exemplify the chemical conversion of renewable CO 2 into valuable products.…”
Section: Introductionmentioning
confidence: 99%